CMV Infection and CMV-Specific Immune Reconstitution Following Haploidentical Stem Cell Transplantation: An Update - Luo, Xiao-Hua; Zhu, Yan; Chen, Yu-Ting; Shui, Li-Ping; Liu, Lin (Frontiers in Immunology, 2021)
Haploidentical stem cell transplantation (haploSCT) has advanced to a common procedure for treating patients with hematological malignancies and immunodeficiency diseases. However, cure is seriously hampered by cytomegalovirus (CMV) infections and delayed immune reconstitution for the majority of haploidentical transplant recipients compared to HLA-matched stem cell transplantation. Three major approaches, including in vivo T-cell depletion (TCD) using antithymocyte globulin for haploSCT (in vivo TCD-haploSCT), ex vivo TCD using CD34 + positive selection for haploSCT (ex vivo TCD-haploSCT), and T-cell replete haploSCT using posttransplant cyclophosphamide (PTCy-haploSCT), are currently used worldwide. We provide an update on CMV infection and CMV-specific immune recovery in this fast-evolving field. The progress made in cellular immunotherapy of CMV infection after haploSCT is also addressed. Groundwork has been prepared for the creation of personalized avenues to enhance immune reconstitution and decrease the incidence of CMV infection after haploSCT.